The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae) - Eguchi, K.; Yoshimura, M.; Yamane, S. (Zootaxa, 2006)
Ten species of the proceratiine ant genus Probolomyrmex are recognized in the Oriental Region: bidens Brown, dammermani Wheeler, itoi sp. nov., longinodus Terayama et Ogata, longiscapus Xu et Zeng, maryatiae sp. nov., okinawensis Terayama et Ogata, procne Brown, vieti sp. nov. and watanabei Tanaka. The ten species and two Australian species can be classified into two species groups. The longinodus group is characterized by the petiole which is clearly longer than high, and subpetiolar process which is low with poorly developed posteroventral portion. The greavesi group is characterized by the petiole which is at most a little longer than high, and subpetiolar process which is developed and somewhat rectangular. Males of dammermani and longiscapus, and queens of dammermani, longinodus, longiscapus and watanabei were described for the first time. A key to the Oriental species of the genus is also given.
Owner: AdminNUSAdded to JabRef: 2013.06.08
Keywords: Formicidae; oriental; Probolomyrmex; Proceratiinae